POTENSI PERAN FARMASIS DALAM MENINGKATKAN KUALITAS HIDUP PASIEN LANJUT USIA: PERSPEKTIF RAWAT RUMAH - Dyah Aryani Perwitasari; Arief Muttaqien (Universitas Ahmad Dahlan, 2012)
The Home Health Care program is getting popular as well. One of the outcomemeasured in this program is patient’s quality of life. Home Health Care program is amultidisciplin program, which need the pharmacist role. The aim of this study was tofind out the potencial pharmacist role in increasing elderly patients’quality of lifeparticipated in Home Health Care program. This study used descriptive design withprospective data sampling. (World Health Organization Quality of Life) We usedWHOQoL as the instrument. The study period was conducted for 13 week in 2009 byvisiting the patients at their homes. The patients were participated in Home HealthCare program of Dr Sardjito hospital, Yogyakarta. Data was descriptively analized.We're recruited seven subjects in this study. In average, their quality of life was low(46,1±4,4). All of the patients received polypharmacy and were found the patientsincompliance in taking the medicines. The role of pharmacist were important in HomeHealth Care program for elderly patients to increase their quality of life. Thepharmacists are supposed to do the drug used monitoring, especially to the elderlypatients with polypharmacy. The advance technique for communication, information,and education is suggested to the pharmacist in this program.